Penerapan Manajemen Persediaan dalam Mengantispasi Kerugian Bahan Baku pada Martabak Putri Naura - Ridwan, Adhrian Fdla; Hana Humaeroh; Tiara Rahmawati; Melani Rambue Basae; Ujang Suherman (Business and Investment Review, 2024)
This research aims to determine the implementation of merchandise inventory management and determine the efforts made to anticipate losses of Martabak Putri Naura merchandise. The type of research used is qualitative and the source of information in this research is the owner of Martabak Putri Naura. The research results show that Martabak Putri Naura has not yet established inventory management in an optimal way. This can be seen from the lack of special considerations made by the owner in providing merchandise to be marketed on weekdays. The owner only considers people's needs which are expected to increase on certain days such as national holidays where the owner provides goods in greater quantities than usual. Sales personnel also play a very important role in marketing the products and services that will be sold. The importance of the role of the sales force must be balanced with sales ability so that it can further support the success of Martabak Putri Naura. With sales ability, consumers can find out about the products offered and sell effectively so that the sales effectiveness of Martabak Putri Naura products can be increased. Apart from that, in marketing these products, sales personnel must also improve their skills in interacting with potential customers or consumers. This is expected to increase sales of Martabak Putri Naura products so that sales effectiveness can also be increased.